2016
DOI: 10.1177/0972150915619809
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Financial Development and Economic Growth in Lao PDR

Abstract: The relationship between financial development and economic growth is not conclusive in existing economics literature. The aim of this paper is to test two hypotheses: 'supply-leading' hypothesis and 'demand-following' hypothesis, using Laos time series data. The ARDL bounds testing approach to cointegration is used to carry out this task. Our results confirm the presence of feedback effect between both variables. Financial development promotes economic growth and in resulting, economic growth leads financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 78 publications
6
28
0
1
Order By: Relevance
“…As such, this stage of development hypothesis as proposed by Patrick (1966) explains bidirectional causality between finance and growth which initiates the third finance-growth nexus view of "feedback hypothesis". This bidirectional view or feedback hypothesis is supported by existing studies such as: Calderon and Liu (2003), Ndako (2010), Ogbonna et al (2013), Hassan, Sanchez, and Yu (2011), Adeyeye et al (2015), Kyophilavong, Uddin, and Shahbaz (2016), and Abosedra and Sita (2018), among others.…”
Section: Causality Views On Finance-growth Nexussupporting
confidence: 71%
“…As such, this stage of development hypothesis as proposed by Patrick (1966) explains bidirectional causality between finance and growth which initiates the third finance-growth nexus view of "feedback hypothesis". This bidirectional view or feedback hypothesis is supported by existing studies such as: Calderon and Liu (2003), Ndako (2010), Ogbonna et al (2013), Hassan, Sanchez, and Yu (2011), Adeyeye et al (2015), Kyophilavong, Uddin, and Shahbaz (2016), and Abosedra and Sita (2018), among others.…”
Section: Causality Views On Finance-growth Nexussupporting
confidence: 71%
“…Not surprisingly, over the last decade, the financial development and economic growth nexus has drawn immense attention among researchers and policymakers from both the developed and developing countries. A number of studies have been conducted to investigate different proxy variables of financial development and empirical studies have confirmed the positive association between them [see, for example, (Azam et al 2016;Bwire and Musiime 2015;Chang and Caudill 2005;Comin and Nanda 2014;De Gregorio and Guidotti 1995;Kassimatis 2000;Kyophilavong et al 2016;Ram 1999;Hasan and Barua 2015;Saad 2014;Shahbaz et al 2015)]. The contribution of financial development towards economic development comes with either bank-based financial development, market-based financial development, or both.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical studies of Ndlovu (2013), Tyavambiza and Nyangara (2015), and Michalopoulos et al (2011) support these findings; however, Bara and Mudxingiri (2016) found a positive association between them that was insignificant. The Economic Development theory explains that an efficient and well-functioning financial sector accelerates the capital accumulation process, which leads to economic development (Kyophilavong et al 2016). The development of the banking sector in Bangladesh has played a significant role in economic development through financial improvements.…”
Section: Domestic Credit From Private Sector (Dcb) As a Proxy For Finmentioning
confidence: 99%
“…The existing literature suggests that the development of the financial sector has a strong association with economic growth (Asghar and Hussain 2014;Bwirea and Musiime 2015;Comin and Nanda 2014;Duasa 2014;Hye and Islam 2013;Jedidia et al 2014;Khoutem et al, 2014;Kyophilavong et al 2016;Masuduzzaman 2014;Mhadhbi 2014;Ndlovu 2013;Rana and Barua 2015;Saad 2014aSaad , 2014bSunde 2013;Uddin et al, 2014a, b). This association exists because an efficient financial system allows for the effective mobilization of economic resources with higher productivity.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%